Session II: The Impact of International Copyright Treaties and Trade Agreements on the Development of Domestic Norms - Gendreau, Ysolde (The Columbia Journal of Law & the Arts, 2017)
These remarks are a transcript of a talk that was given on October 14, 2016, at the Kernochan Center Annual Symposium at Columbia Law School. Session II addressed how international copyright treaties and FTAs affect national IP laws in the U.S. and elsewhere. Session Panelists: Krista Cox, Director of Public Policy Initiatives, Association of Research Libraries (ARL) Ysolde Gendreau, Professor, Université de Montréal Eric J. Schwartz, Partner, Mitchell, Silberberg & Knupp LLP and Counsel to the International Intellectual Property Alliance Karyn Temple Claggett, Associate Register of Copyrights and Director of Policy & International Affairs, U.S. Copyright Office